The Influence Of Board Characteristics On The Financial Performance Of Listed Companies In Malaysia - Lai, Ying Zhe (2022)
The research study is aimed to examine how the board characteristics influence on the financial performance of public listed companies in Malaysia from the year 2011 to the year 2020. Therefore, 85 listed companies in Malaysia have been selected to be examined in this research study. For measuring the financial performance, ROA and ROE are being used to measure the firm performance. The board characteristics variables included in this research study are board size, female directors, independent directors, international experience directors, and CEO duality. Besides, the company size will be the control variable in the research study. Panel analysis will be used in this research study, it consists of the pooled panel regression analysis, Random Effect Model, Fixed Effect Model, Hausman test, and Wald test. The analysis has been discussed based on the result of each of the variables. Then, the pooled panel regression analysis indicates that the variables of female directors, international experienced directors, independent directors, and CEO duality have a positive and significantly relationship with the firm performance. The board size variable has no significant relationship with the firm performance, based on the pooled panel regression analysis. Moreover, the company size is found that there is a negative and significant relationship with company performance. Therefore, based on the study, it can be concluded that not all board characteristics have relationship to firm performance, but there are some board characteristics are able to influence the financial performance of the listed companies positively and negatively. Moreover, this research study also suggests that the future study of this research study can be explored by providing more variables to examine that how the board characteristics influence on the financial performance of public listed companies.